DAYA DUKUNG KAWASAN DAN PERSEPSI PENGUNJUNG WISATA BAHARI DI PANTAI JEMELUK, KARANGASEM, BALI - Lidya Permata Sari Silitonga; I Wayan Arthana; I Wayan Darya Kartika (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
This study aims to examine the carrying capacity of the area as well as visitor perceptions of marine tourism activities at Jemeluk Beach, Karangasem, Bali, as a basis for sustainable tourism management. Data collection was carried out from late September to late October 2023 using quantitative and qualitative descriptive approaches, with primary data obtained through observations, interviews, and questionnaires, and secondary data gathered from literature and related institutions. The carrying capacity analysis was conducted by considering the extent of the usable area and the duration of visitor activities, while visitor perceptions were evaluated using the four main components of tourism—attraction, accessibility, amenities, and ancillary services (4A)—measured with the Likert Scale. The results showed that beach recreation has a carrying capacity of 44 people/day, snorkeling 385 people/day, and diving 181 people/day, with a total carrying capacity of 610 people/day. Overall, visitors’ perceptions of attractions were classified as good, particularly for snorkeling and diving, which were appreciated due to the diversity of coral reefs and clear water conditions. Accessibility, amenities, and ancillary services were assessed as adequate, although several aspects such as road conditions, availability of worship facilities, and information centers still require improvement. These findings are expected to serve as valuable input for tourism managers and local government in enhancing service quality and ensuring sustainable utilization of natural resources at Jemeluk Beach.